The risk reduction of recurrent periodontal pathogens of local application minocycline HCl 2% gel, used as an adjunct to scaling and root planing for chronic periodontitis treatment - Soeroso Y; Akase T; Sunarto H; Kemal Y; Salim R; Octavia M; Viandita A; Setiawan J; Bachtiar BM (Dove Medical Press, 2017)
Y Soeroso,1,2 T Akase,3 H Sunarto,1,2 Y Kemal,1 R Salim,1 M Octavia,1 A Viandita,1 J Setiawan,1 BM Bachtiar2,4 1Department of Periodontology, Faculty of Dentistry, Universitas Indonesia, Jakarta, Indonesia; 2Oral Sciences Research Center, Universitas Indonesia, Jakarta, Indonesia; 3R&D, Oral Care Company, Sunstar Group, Takatsuki City, Japan; 4Department of Oral Biology, Faculty of Dentistry, Universitas Indonesia, Jakarta, Indonesia Background: The aim of this study was to evaluate the clinical and microbiological effects of local application minocycline HCl 2% gel, used as an adjunct to scaling and root planing (SRP) for treatment of chronic periodontitis (CP). CP is an inflammation of periodontal tissue that is caused mainly by bacterial infection, where periodontal destruction such as loss of attachment and bone destruction occurred. Methods: A total of 81 subjects with moderate to severe periodontitis whose baseline clinical attachment loss (CAL) was ≥4 mm were randomly assigned to receive SRP alone (control group, N=39) or SRP followed by four times of local application of minocycline HCl gel (Periocline) once a week (test group, N=42). Pocket depth, CAL, and papilla bleeding index were examined at baseline, 21 days, 2, 3, and 6 months. Subgingival plaque samples were collected with sterile curettes and were analyzed by real-time polymerase chain reaction for the presence of three periodontal pathogens (Porphyromonas gingivalis [P.g.], Tannerella forsythia [T.f.], and Treponema denticola [T.d.]) at baseline, 2, 3, and 6 months. Results: The number of bacteria was reduced in both groups at 2 months after baseline (SRP treatment). The changes (2–6 months) in T.d. and T.f. counts in the test group were significantly lower than those in the control group. In the control group, a significant regrowth of P.g., T.f., and T.d. was observed from 2 to 6 months and of P.g. and T.f. from 3 to 6 months. On the other hand, in the test group, the number of the three bacteria did not significantly increase during the 6-month period. Conclusion: The results showed that local application of minocycline, used as an adjunct to SRP, was effective for suppressing regrowth of periodontal pathogens, suggesting its risk reduction of recurrent periodontal pathogens in CP. Keywords: chronic periodontitis, minocycline, scaling and root planing, real-time PCR, periodontal pathogen